2014
DOI: 10.1074/jbc.m114.612929
|View full text |Cite
|
Sign up to set email alerts
|

Polynucleotide 3′-terminal Phosphate Modifications by RNA and DNA Ligases

Abstract: Background: Classic RNA ligases join 5ЈpRNA to RNA3ЈOH. Results: Thermophilic RNA ligases were able to modify ssDNA or RNA with a 3Ј-phosphate. Conclusion: Thermophilic ligases form RNA 2Ј,3Ј-cyclic phosphate and ssDNA 3Ј pp 5Ј A. Significance: Thermophilic RNA ligases duplicate the enzymatic function of RtcA and may have an important role in nucleic acid 3Ј-phosphate biology in addition to conventional ligation of 5ЈpRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Although the physiological substrate and biological function of Rnl3 are not known, it can act to circularize single-stranded RNA and DNA ( 7 , 18 ). Methanobacterium thermoautotrophicum Rnl3 (MthRnl) can also convert 3′-phosphorylated RNA termini into 2′, 3′-cyclic phosphate ( 19 ). Under a non-optimal condition, MthRnl can remove the 5′-adenylate on AppRNA to generate 5′-PO 4 RNA ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the physiological substrate and biological function of Rnl3 are not known, it can act to circularize single-stranded RNA and DNA ( 7 , 18 ). Methanobacterium thermoautotrophicum Rnl3 (MthRnl) can also convert 3′-phosphorylated RNA termini into 2′, 3′-cyclic phosphate ( 19 ). Under a non-optimal condition, MthRnl can remove the 5′-adenylate on AppRNA to generate 5′-PO 4 RNA ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is considerable plasticity in the direction of the RtcA pathway (2′,3′ cyclization versus 5′ A capping), with attendant uncertainty as to what the ‘real’ substrates of RtcA are. This theme is amplified by the recent report of Zhelkovsky and McReynolds ( 27 ) that certain classic ATP-dependent thermophilic RNA ligases, which join 3′-OH/5′-PO 4 ends via an AppRNA intermediate, are also capable of adenylylating a DNA 3′-PO 4 end to form a stable DNAppA product. In effect, the thermophilic RNA ligases double as DNA 3′ capping enzymes, albeit with an A cap rather than a G cap.…”
Section: Resultsmentioning
confidence: 99%
“…In effect, the thermophilic RNA ligases double as DNA 3′ capping enzymes, albeit with an A cap rather than a G cap. Following on our discovery of aprataxin as a DNAppG 3′ de-capping enzyme, they found that Saccharomyces cerevisiae aprataxin removes the A cap from DNAppA ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Initially described as an adenylate decapping enzyme acting on abortive AppDNA intermediates formed by ATP-dependent DNA ligases, aprataxin was subsequently shown to have 3= decapping activity on a DNAppG end formed by E. coli RtcB (12,24) and on DNAppA ends generated by an ATP-dependent thermophilic RNA ligase (38). Here, we extend the aprataxin repertoire by showing that it can remove a 5= guanylate cap from GppDNA formed by M. xanthus RtcB3.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, there is considerable plasticity in the direction of the RtcA pathway (2=,3= cyclization versus 5= A capping), with resulting uncertainty as to what the real substrates of RtcA are. This theme was amplified by the report that certain classic ATP-dependent thermophilic RNA ligases, which join 3=-OH/5=-PO 4 ends via an AppRNA intermediate, are also capable of adenylylating a DNA 3=-PO 4 end to form a stable DNAppA product (38). In effect, the 32 P-labeled 24-mer, 12-mer, or 6-mer pDNA OH substrates or 0.1 M 5= 32 P-labeled 12-mer pRNA OH substrate (with nucleotide sequences as shown), and 1 M RtcB3 were incubated at 30°C.…”
Section: Discussionmentioning
confidence: 99%